PELATIHAN PERAWATAN JENAZAH PEREMPUAN DI DUSUN JENENGAN PONDOKREJO, TEMPEL, SLEMAN, DIY - Tulasmi Tulasmi; Anom Garbo (Politeknik Negeri Sriwijaya, 2022)
Every creature that has a life, including humans, will taste death. Caring for the corpse is a kifayah obligation that Muslims must carry out for Muslims who died. In Islamic law, caring for the corpse includes bathing, shrouding, praying, and burying. However, the facts show that not all community members understand and can practice treating corpses according to Islamic law. Therefore, this training in caring for women's bodies is expected to contribute knowledge and skills to assist the community in caring for women's bodies. So that in the end, there will be a group of volunteers who can overcome the problem of caring for women's bodies that the people of Jenengan have faced. There are three steps used in this training to care for women's bodies, namely the lecture method, discussion, and practice of managing the corpse, which is equipped with adequate instruments. As a result, there is an increase in the understanding of the training participants, marked by the willingness to initiate the formation of a group of volunteers to care for corpses